Psychological Science in the Wake of COVID-19: Social, Methodological, and Metascientific Considerations. (March 2022) - Rosenfeld, Daniel L.; Balcetis, Emily; Bastian, Brock; Berkman, Elliot T.; Bosson, Jennifer K.; Brannon, Tiffany N.; Burrow, Anthony L.; Cameron, C. Daryl; Chen, Serena; Cook, Jonathan E.; Crandall, Christian; Davidai, Shai; et al.
The COVID-19 pandemic has extensively changed the state of psychological science from what research questions psychologists can ask to which methodologies psychologists can use to investigate them. In this article, we offer a perspective on how to optimize new research in the pandemic's wake. Because this pandemic is inherently a social phenomenon—an event that hinges on human-to-human contact—we focus on socially relevant subfields of psychology. We highlight specific psychological phenomena that have likely shifted as a result of the pandemic and discuss theoretical, methodological, and practical considerations of conducting research on these phenomena. After this discussion, we evaluate metascientific issues that have been amplified by the pandemic. We aim to demonstrate how theoretically grounded views on the COVID-19 pandemic can help make psychological science stronger—not weaker—in its wake.